Population Density in Hiroshima and Nagasaki Before the Bombings in 1945: Its Measurement and Impact on Radiation Risk Estimates in the Life Span Study of Atomic Bomb Survivors. Issue 8 (29th March 2018) - French, Benjamin; Funamoto, Sachiyo; Sugiyama, Hiromi; Sakata, Ritsu; Cologne, John; Cullings, Harry M; Mabuchi, Kiyohiko; Preston, Dale L
Abstract: In the Life Span Study cohort of atomic bomb survivors, differences in urbanicity between high-dose and low-dose survivors could confound the association between radiation dose and adverse outcomes. We obtained data on the population distribution in Hiroshima and Nagasaki before the 1945 bombings and quantified the impact of adjustment for population density on radiation risk estimates for mortality (1950–2003) and incident solid cancer (1958–2009). Population density ranged from 4, 671 to 14, 378 people/km 2 in the urban region of Hiroshima and 5, 748 to 19, 149 people/km 2 in the urban region of Nagasaki. Radiation risk estimates for solid cancer mortality were attenuated by 5.1% after adjustment for population density, but those for all-cause mortality and incident solid cancer were unchanged. There was no overall association between population density and adverse outcomes, but there was evidence that the association between density and mortality differed according to age at exposure. Among survivors who were 10–14 years of age in 1945, there was a positive association between population density and risk of all-cause mortality (per 5, 000-people/km 2 increase, relative risk = 1.053, 95% confidence interval: 1.027, 1.079) and solid cancer mortality (per 5, 000-people/km 2 increase, relative risk = 1.069, 95% confidence interval: 1.025, 1.115). Our results suggest that radiation risk estimates from the Life Span Study are not sensitive to unmeasured confounding by urban-rural differences.